The literary prose of Italian Switzerland as a corpus for the study of Helvetisms: An exploratory survey based on Infanzia e bestiario by Claudia Quadri - Durkiewicz, Maciej (Kwartalnik Neofilologiczny, 2026)
The paper examines literary prose as a corpus for the study of Helvetisms, taking Infanzia e bestiario by Claudia Quadri as a case study. By integrating corpus-based and corpus-driven approaches, the analysis verifies the presence of already attested Helvetisms and identifies lexical units not recorded in existing reference works, which are considered candidates for Helvetism status. The results highlight the value of narrative prose as a valid observatory of the lexicon of Swiss Italian.